Infertility treatment and autism risk using the Modified Checklist for Autism in Toddlers (M-CHAT). Issue 3 (12th March 2020) - Robinson, S L; Parikh, T; Lin, T; Bell, E M; Heisler, E; Park, H; Kus, C; Stern, J E; Yeung, E H
Abstract: STUDY QUESTION: Are toddlers conceived by fertility treatment at higher risk of failing a screening tool for autism spectrum disorders (ASD) than toddlers not conceived by treatment? SUMMARY ANSWER: Compared with children not conceived by infertility treatment, children conceived by any infertility treatment, ovulation induction with or without intrauterine insemination (OI/IUI), or assisted reproductive technologies (ART) appeared to have had higher odds of failing an ASD screening; however, results were inconclusive and need replication. WHAT IS KNOWN ALREADY: Although most of the studies which have examined risk of ASD after ART show no association, the results are mixed. Thus, further studies are needed to clarify this association. STUDY DESIGN SIZE, DURATION: The Upstate KIDS Study is a population-based, prospective cohort study of children born in New York State between 2008 and 2010. Children were screened for ASD using the Modified Checklist for Autism in Toddlers (M-CHAT) at ages 18 and 24 months. PARTICIPANTS/MATERIALS, SETTING, AND METHODS: The New York State live-birth registry was used to identify newborns conceived with and without fertility treatment with a 1:3 ratio, frequency matched on region of birth. At 18 and 24 months, 3183 and 3063 mothers, respectively, completed the M-CHAT questionnaire. The current analysis included 2586 singletons and 1296 twins with M-CHAT information at 18 and/or 24 months. Multivariable logistic regression with generalized estimating equations (GEE) was used to estimate odds ratios (aOR) and 95% confidence intervals (CI) after adjustment for covariates such as maternal age, education and plurality. MAIN RESULTS AND THE ROLE OF CHANCE: We found that 200 (5.2%) and 115 (3.0%) children failed the M-CHAT at 18 and 24 months, respectively. The associations between use of infertility treatment and failing the M-CHAT at 18 and/or 24 months were positive but inconclusive as they failed to exclude no association (18 months aOR 1.71, 95% CI: 0.81–3.61; 24 months aOR 1.78, 95% CI: 0.66–4.81; and both 18 and 24 months aOR 1.53, 95% CI: 0.78–2.99). The relationships between OI/IUI and ART with M-CHAT failure at 18 and/or 24 months were similar to those of using any fertility treatment. In vitro fertilization with intracytoplasmic sperm injection was not consistently positively or inversely associated with M-CHAT failure at each time point (18 months aOR 1.20, 95% CI: 0.51–2.83; 24 months aOR 0.93, 95% CI: 0.37–2.31; and both 18 and 24 months aOR 1.09, 95% CI: 0.50–2.60). LIMITATIONS REASONS FOR CAUTION: The M-CHAT is a screening tool used for ASD risk assessment, and therefore, M-CHAT failure does not indicate ASD diagnosis. In addition, we did not have power to detect associations of small magnitude. Finally, non-response to follow-up may bias the results. WIDER IMPLICATIONS OF THE FINDINGS: Despite lack of precision, the positive associations between ART and M-CHAT failure suggest that larger population-based studies with longer follow-up are needed. STUDY FUNDING/COMPETING INTEREST(S): Supported by the Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD; contracts HHSN275201200005C, HHSN267200700019C). The sponsor played no role in the study design, data collection, data analysis or interpretation, writing of the manuscript or decision to submit the article for publication. There are no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: Not applicable.